A novel lotus seed cross-linked resistant starch: Structural, physicochemical and digestive properties - Li, Lanxin; He, Shuqi; Lin, Yongjie; Zheng, Baodong; Zhang, Yi; Zeng, Hongliang (Frontiers in Nutrition, 2022)
The structural properties and physicochemical characteristics of lotus seed cross-linked resistant starches (LSCSs; LS-0CS, LS-1CS, LS-2CS, LS-4CS, LS-6CS, LS-8CS, LS-10CS and LS-12CS) with different concentrations of cross-linking agents were investigated. The degrees of cross-linking of LSCSs increased along with the amount of cross-linking agent. The higher the degree of cross-linking, the greater the degree of LSCSs granule agglomeration. The occurrence of the cross-linking reaction was confirmed by the appearance of P=O at 1,250 cm−1 as assessed by FT-IR, and the covalent bonds formed by the phosphate group in LSCSs were mainly composed of distarch monophosphate (DMSP) as determined by 31P NMR. As the crosslinking degree increased, the peak strength of DMSP in starch was stronger and the specific gravity of DMSP was larger. Among the samples, LS-12CS had the highest cross-linking degree, with a greater specific gravity of DMSP. Moreover, the solubility levels of LSCSs decreased and the thermal stability and anti-digestive properties improved as the cross-linking degree increased, which was correlated with the degree of agglomeration and DMSP in LSCSs. The RS content of LS-12CS was 48.95±0.86%.